Characteristics of frankfurters from preblended pork - Kastner, Curtis L.; Choi, Y.I.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Five pork carcasses were used to determine the effects of hot boning and various combinations of salt (0, 1.5, or 3.0%) and a phosphate mixture (0 or 0.5%) on functional, processing, and storage characteristics of preblended pork (preblends). Although hot-boned (HB) preblends had superior functional properties compared to conventionally boned (CB) preblends, HB and CB frankfurters had similar characteristics. More (P(.05) myosin and actin (proteins that cause lean and fat particles to bind together) were extracted from HB than CB preblends. Addition of salt (1.5 or 3.0%) or phosphate (0.5%) generally increased myosin and actin extraction in both HB and CB preblends. Salt levels can be reduced from 3.0 to 1.5% in frankfurters without any processing or storage difficulties, if phosphate is added. Some model system measurements could be used to predict relative processing yield of raw materials.
Keywords: Swine; Frankfurters; Preblended pork